For the Love of the Child: Bestowing Value amidst Inconsistent Inclusive Education Beliefs and Practices for One Student with Severe Disabilities - Mooney, Laura Rae; Lashewicz, Bonnie (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> In this article, we chart developments of inclusive education practice and policy in Alberta, Canada, and conclude that much remains to be done toward achieving an educational system where all students, including those with severe disabilities, feel welcome and valued. We argue a need for deeper understandings of parent and educator beliefs about, and practices of, inclusive education in order to promote “mutual adaptation,” built on shared beliefs and consistent practices. To this end, we present an instrumental case study examination of the inclusion experience of one Canadian student with a severe disability described from multiple parent and educator perspectives. We call attention to inconsistencies in educator beliefs and practices, yet we draw out shared beliefs rooted in “love of the child.” Our study derives from Paulo Freire’s understanding of love as key to educational pedagogy (1968/1970, 2005), and we uphold love as a point of convergence for parents, educators, and other educational stakeholders striving for more consistent approaches to inclusive education.